Testing the validity of the J-curve hypothesis between Brazil and the USA - Ongan Serdar; Pabuçcu Hakan (Atlantic Review of Economics, 2017)
This paper aims to investigate the validity of the J-curve hypothesis between Brazil and the USA using quarterly data for the period of 1981Q1- 2015Q1. To achieve this aim, the vector error correction (VEC) with cointegration, NARX (non-linear autoregressive exogenous) and ANFIS (adaptive neuro-fuzzy inference system) models are separately applied to strengthen this investigation. NARX and ANFIS, as artificial neural networks (ANN) models, were used for the first time in this study to test the validity of the J-curve hypothesis. It was found that the real exchange rate and income, as the independent variables, and the trade balance between Brazil and the USA, as the dependent variable, are cointegrated in the long-run. The empirical findings of all testing models examined in this study indicate that the J-curve hypothesis is not valid between Brazil and the USA. The real depreciations of the Brazilian currency do not make a positive contribution to the trade balance for Brazil.
Keywords: F10; F14; F31; 330; J-curve hypothesis; VECM with cointegration; NARX; ANFIS; Brazil; USA